2018
DOI: 10.1371/journal.pone.0202597
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the nigrostriatal pathway in a 6-OHDA rat model of Parkinson’s disease evaluated with multimodal MRI

Abstract: Parkinson’s disease is characterized by neurodegeneration of the dopaminergic neurons in the substantia nigra pars compacta. The 6-hydroxydopamine (6-OHDA) rat model has been used to study neurodegeneration in the nigro-striatal dopaminergic system. The goal of this study was to evaluate the reliability of diffusion MRI and resting-state functional MRI biomarkers in monitoring neurodegeneration in the 6-OHDA rat model assessed by quantitative histology. We performed a unilateral injection of 6-OHDA in the stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
4
22
0
1
Order By: Relevance
“…The 6-OHDA model is a classic and widely used neurotoxin rodent model of PD. The bilateral administration of 6-OHDA into the striatum induces retrograde neuronal cell death of the tyrosine hydroxylase (TH)-containing neurons in the substantia nigra pars compacta (SNc) mimicking Parkinson-like pathology [ 56 , 57 ]. Here, the animals were anesthetized with ketamine (100 mg/kg) and xylazine (10 mg/kg) intraperitoneally and placed in the stereotactic device (EFF 331-Insight™, Ribeirão Preto, São Paulo, Brazil) ( Figure 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…The 6-OHDA model is a classic and widely used neurotoxin rodent model of PD. The bilateral administration of 6-OHDA into the striatum induces retrograde neuronal cell death of the tyrosine hydroxylase (TH)-containing neurons in the substantia nigra pars compacta (SNc) mimicking Parkinson-like pathology [ 56 , 57 ]. Here, the animals were anesthetized with ketamine (100 mg/kg) and xylazine (10 mg/kg) intraperitoneally and placed in the stereotactic device (EFF 331-Insight™, Ribeirão Preto, São Paulo, Brazil) ( Figure 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…The neurotoxin 6-OHDA is one of the proposed for modeling PD research in animal models [ 74 ]. The administration of 6-OHDA is variably unilateral into the nigrostriatal pathway to produce neurodegeneration, and various 6-OHDA animal models have been conventional for the PD investigations [ 75 , 76 ]. 6-OHDA is a lethal toxin that mainly damages peripheral and central nervous systems [ 77 ].…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…A voxel-based analysis of a 7 T DTI study in marmosets before and after MPTP administration revealed increased diffusivity in the bilateral nigrostriatal pathway, validated by ex-vivo microscopic tractographic images, which showed loss of fiber structures in the MPTP-treated brain (Hikishima et al, 2015 ) and a longitudinal combined morphometric and DTI study in cynomolgus monkeys revealed widespread and dynamic structural changes not only in the nigrostriatal pathway but also in other cortical, subcortical, and cerebellar areas (Jeong et al, 2018 ). Further DTI studies (within multimodal imaging protocols) demonstrated significantly altered diffusivity parameters (MD, AD, RD) in the nigrostriatal tract (in correlation with MPTP dose), but not in the substantia nigra or striatum, in the macaque nemestrina after application of MPTP (Shimony et al, 2018 ) and increased FA in the ipsi- and contralateral striatum after 3 weeks and increase of AxD and MD in the ipsilateral striatum in rats with 6-OHDA striatal lesions (Perlbarg et al, 2018 ). That way, DTI applications to various PD models could contribute to the mapping of the underlying pathophysiology, together with DKI as a non-Gaussian DTI approach, which demonstrated microstructural alterations when applied to transgenic mice overexpressing human wildtype a-synuclein under the murine Thy-1 promoter, that is, increases in the striatum and thalamus after 3 months and in the substantia nigra after 6 months (Khairnar et al, 2017 ).…”
Section: Applications To Models Of Neurodegenerative Diseasesmentioning
confidence: 99%